(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents modern, innovative methods of teaching engineering and computer graphics to students studying in the field of water management and land reclamation. The shortcomings of traditional methods are analyzed and an improved teaching methodology based on the use of AutoCAD graphics software is proposed. The effectiveness of this method is proven on the basis of practical experience.